Technical efficiency of the driftnet and Payang seine (lampara) fisheries in West Sumatra, Indonesia - Zen, Linda Waty; Raja Abdullah, Nik Mustapha; Yew, Tai Shzee (Asian Fisheries Society, 2002)
This paper examines the production structure of the multi-species, multi-gear fishery in West Sumatra, Indonesia. Majority of the fishermen in this area are still living below the poverty level. This phenomenon is often attributed to low productivity and inefficient use of fishing inputs. Two important fishing gears, driftnet and Payang seine (lampara) were chosen for this study. Using the translog stochastic frontier production function, it was found that about 70 and 100% of the driftnet and lampara fishing units, respectively achieved 90% or even higher technical efficiency. This implies that expansion in fish production for driftnet fishery is still possible by adopting the technology of the highly experienced or well trained fishermen and through optimal resource allocation, although lampara fishery has been operating at the optimal level. Policies to increase fish catch should therefore be focused on driftnet fishing, while effort reduction measures on the other hand should be imposed on lampara fishery.